2023
DOI: 10.4103/njms.njms_446_21
|View full text |Cite
|
Sign up to set email alerts
|

Students’ preparedness and perception toward online learning in dental education – A cross-sectional study

Shrivardhan Kalghatgi,
Mahesh Ravindra Khairnar,
Tanushri Mahendra Dalvi
et al.

Abstract: Background: Amid the health risk posed by coronavirus disease 2019 pandemic, all the educational institutions in India have adopted online teaching as a method of imparting education. Thus, the current study was executed to evaluate the perception and preparedness of dental students toward online learning in dental education. Materials and Methods: The present cross-sectional study was conducted on 286 dental undergraduate (UG) and postgraduate (PG) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…One student actually reported that his ability to grasp concepts during e-learning session is significantly reduced compared to face-to-face instruction. These concerns align with previous studies that have identified similar challenges faced by students in e-learning environments ( 20–22 ). In fact, prior literature has shown that prolonged engagement with online platforms can lead to e-learning fatigue, which affects both faculty and students ( 22–26 ).…”
Section: Discussionsupporting
confidence: 90%
“…One student actually reported that his ability to grasp concepts during e-learning session is significantly reduced compared to face-to-face instruction. These concerns align with previous studies that have identified similar challenges faced by students in e-learning environments ( 20–22 ). In fact, prior literature has shown that prolonged engagement with online platforms can lead to e-learning fatigue, which affects both faculty and students ( 22–26 ).…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, web-based learning, also known as e-learning, has gained popularity as a method of delivering education in dentistry, thanks to technological advancements [ 5 , 6 ]. This approach provides learners with access to a wealth of information while offering the flexibility to learn at their own pace, overcoming the limitations of time and space [ 7 ].…”
Section: Introductionmentioning
confidence: 99%